KEPEMIMPINAN BERBASIS ASTA BRATA DAN SIFAT SIDDIQ PADA PENGELOLA USAHA MIKRO KELUARGA: STUDI ETNO-RELIGIUS DI SENTRA INDUSTRI BATIK: Asta Brata Leadership and the Principle of Siddiq in Family-Owned Microenterprises: An Ethno-Religious Study of Batik Industry Centers - Syahrul Syarifudin (tesco publisher, 2025)
This study aims to explore and develop a hybrid leadership model that integrates Javanese local wisdom (Asta Brata) with Islamic business ethics (Sifat Siddiq) in family-based Micro, Small, and Medium Enterprises (MSMEs). Amidst global economic dynamics, family-based MSMEs often face succession and professionalism challenges rooted in a crisis of trust. This study uses a qualitative approach with a phenomenological case study method in the batik industry center in Central Java. Data were collected through in-depth interviews, participant observation, and documentation studies of 15 hereditary batik business owners. The results show that the internalization of Asta Brata values—particularly the elements of the Sun (Surya) and Earth (Bantala)—which are synergized with the nature of Siddiq (honesty/integrity) form a